Limit states of thin-walled composite structures with closed sections under axial compression - Rozylo, Patryk (Composites. Part B, Engineering, 2024)
The subjects of the study were thin-walled composite columns with closed cross sections manufactured using the autoclave technique. The composite profiles were characterized by the fact that they had a constant height and arrangement of laminate layers, however, varied cross-sectional shapes. The study was conducted using several interdisciplinary experimental research methods and advanced numerical simulations. In the course of the research, both forms of structural stability loss were registered, and damage to composite structures was assessed. In the course of the research, the influence of the shape of the cross-section on the stability and load-carrying capacity of the structure was evaluated. A measurable effect of the conducted research was the determination of the structure's post-buckling equilibrium paths, which made it possible to determine the structure's behavior in the full range of loading. In addition, the author's numerical models developed enabled validation of parallel experimental studies. The developed numerical models were based on a failure criterion known as progressive failure analysis - which allowed a thorough assessment of the failure mechanism of the composite material.